Peran Penyuluh Agama Islam dalam Mengatasi Dampak Psikologis Anak Akibat Perceraian Orang Tua Di Desa Sungai Keruh Kecamatan Tebo Tengah Kabupaten Tebo - Shohbihi, M.; Kusnadi, Edy; Nurkhayati, Ayu (UIN Sulthan Thaha Saifuddin Jambi, 2022)
This research was motivated by parental divorce in Sungai Keruh Village, Kec. Central Tebo which resulted in many changes in children both in their physical and psychological conditions. Divorce often causes stress and trauma in children. Apart from that, children often feel restless or anxious when they are in the community. The research approach that the author uses is qualitative research with an emphasis on research that produces qualitative descriptive data in the form of written or spoken words from people and observed behavior. This research uses data collection techniques using 3 techniques, namely observation, interviews and documentation. As a result, the author found that parental divorce affects the psychological state of children and children's behavior, parental divorce also has an impact on children, namely positive and negative impacts, the positive impact of children becoming more optimistic about living their lives and the traumatic experiences experienced by children can make children more resilient and independent. Meanwhile, the negative impacts that arise include children becoming restless, anxious, tending to behave rudely, and having difficulty concentrating. Finally, the author advises all people to work together and care for the growth and development of their children, especially the psychological condition of children after their parents' divorce.